LEGISLATIVE NEGLECT - Rafkat Sh. Urazbaev (Высшее образование в России)
The paper analyzes the Federal Law on Education in the Russian Federation and the articles of the Labor Code of the Russian Federation regulating the specific features of working activity of educators. The author demonstrates irrationality of absence of corruption-related crime among the list of the crimes, which prevent professional educational activity. In the author's view, this gap negatively affects the process of education and character development of the students, and complicates the control of corruption in education.